Proceso didáctico inclusivo en el razonamiento lógico matemático de los estudiantes del séptimo año de Educación General Básica - Jiménez Villamar, Yadira Etelvina (2020)
In the present research Project, the inclusive didactic process in the mathematical logical reasoning of the students of the seventh year of basic education has been applied in the basic education unit “Enrique Ibañez Mora” in order to provide a solution to the problem of lack of understanding and mathematical interpretation of logical reasoning and thus contribute fully to a change in Ecuadorian education. A field study was carried out, using the deductive, inductive, statistical method and the main research techniques that were used as observation, interview and surveys, which reflect the importance of conducting the investigation, which was obtained as a result difficulties in the application of mathematical logical reasoning in problems of daily living………..